FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN SISTEM INFORMASI AKUNTANSI PADA UMKM KOTA MEDAN - Tiffani Aryska Permadi; Indra Fauzi (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2022)
This study aims to determine the effect of accounting knowledge, business scale, business experience, and age of business on the utilization of Accounting Information Systems for MSME actors in the district of Medan Tembung, Medan Denai, and Medan Timur. This research method is quantitative. The population is 228 MSME actors from 3 sub-districts which are assisted by the Medan City Cooperative & MSME service. The sample in this study amounted to 70 respondents. The sampling technique used incidental technique with the slovin formula method. The type of data used is primary data with data collection using the Documentation, Literature study, and Questionnaire/questionnaire methods. Data analysis and hypothesis testing include validity test, reliability test, classical assumption test, coefficient of determination test, f test (simultaneous), and t test (partial). Data analysis used multiple linear regression analysis. The results of this study indicate that accounting knowledge and business age have an effect on the utilization of accounting information systems for MSMEs in Medan City. Meanwhile, business scale and business experience have no effect on the use of accounting information systems for MSMEs in the city of Medan.